Developing critical thinking skills assessment of excretory system - Yenny Anwar; Adeng Slamet; Ayu Tania (Universitas Negeri Jakarta, 2023)
This study aims to developing valid, reliable and practical Assessment to measure or to treat the critical thinkings skills of senior high school students on excretory system. The method used on this study is the development research (DR) that consists of synthesising theory and needs analyzes, step design (variable construction, indicator development, questions arrangement, making the instrumen, scoring and evaluation). Evaluation steps divided into three parts, namely: validation, reliability, and items analyzes. The quality of the test questions was determined by theoretical validation and empirical validation. The quality of the item was analised using the results of a field trial included the difficulty level, discriminatory power, and distractor. This study produced a valid questions in terms of content, construct, and language, with a final koefisien kappa above 0,61. The reliability of the test was 0,84. The result of students questionnaire analyzes in the phase of field trial gained an average of 3,60 (scale of 5). The average of value obtained from the student questionnaire indicates that the Critical Thinking Skills questions of exretory system is easy to use (practical). Thus, the development research produced 32 questions of critical thinking are valid, applicable, and easy to use.